Prevalence and Associated Factors of Gastro-Esophageal Reflux Disease among a Sample of Undergraduate Medical Students in Baghdad - Abdulwahhab, Sarah H.; Al Hashimi, Ban A.R.; Alkhalidi , Nawal M. (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Gastroesophageal reflux disease (GERD) is a commonly prevalent gastrointestinal disorder in adults, it develops when the stomach contents reflux and rise up into the esophagus as a result from lower esophageal sphincter dysfunction. Very few studies on magnitude of GERD in student community have been done. The study aim was conducted to determine the prevalence of GERD among sample of medical students and the potential risk factors associated with it. Method: A cross sectional descriptive study conducted on a sample of 300 undergraduate students of medical college/Baghdad university from 15th of January -1st of June 2020. All participants answered online questionnaire for GERD symptoms. The questionnaire included demographic data like age, gender, height and weight, lifestyle, and dietary habits. Statistical data were analyzed using the Statistical Package for Social Sciences (SPSS) version 25. Results with a P value of <0.05 were considered statistically significant. Results: A total 300 participants of medical students, 216(72%) females & 84 (28%) males participants were evaluated for GERD, the mean (SD) age of the participants was 21.93(1.81)years, the prevalence of GERD was 13.3%, 86 (28.7%) of the participants had positive family history of GERD and had statistical significant association with GERD (P-value=0.001),28(9.3%) were sleeping within one hour of meal/dinner(P-value=0.001),antacids & PPIs takers were 38(12.7%) & 41(13.7%) respectively and had significant statistical association with GERD (P-value=0.001for each of them),20(6.7%) suffered from frequent belching (P-value=0.001).About 10.3% (31) of participants had Oesophageal-Gastro-Dudenoscopy (OGD), it was found statistically significant (P-value=0.03). No significant association between results of GERD score, general characteristics and dietary habits. Conclusions: This study found small prevalence of GERD among participants: Sleeping within one hour of dinner or meal, positive family history of GERD/heartburn/regurgitation, intake of antacids & PPIs for symptoms relief, having Oesphageal-Gastro-Dudenoscopy (OGD) and frequent belching were associated with GERD symptoms, no significant association was found between GERD and dietary habits.